A Special Thermal Fatigue Failure Mode of Pipe in Nuclear Power Plant and Its Countermeasures. Issue 3 (April 2021) - Yin, Qin; Feng, Huixing; Xue, Donglin; Shu, Guo
Abstract: Thermal fatigue phenomenon is well known and feedbacked in the nuclear power industry. Targeted screening principles has been developed and applied. However, a thermal fatigue failure, "Swirl Penetration" of small-diameter pipeline, was identified through a Reactor Coolant System (RCS) leakage in a nuclear power plant. Unexpectedly, this failure is not within the scope of previous screening principles of thermal fatigue. It is characterized in that the high-temperature main piping is connected downward with a certain length of vertical small-diameter piping, and then the vertical piping turns horizontally through an elbow. The reactor coolant in the lower pipeline does not flow under normal operation conditions. Subject to long-term cyclic thermal fatigue, cracks initiate and propagate in the elbow. Through researches, corrective measures are put forward to prevent, mitigate or discover it.